Force analysis of the planetary Hypocycloid roller gears - Nguyen, Hồng Thái; Le, Hiếu Giang; Thach, Dũng Chinh (Journal of Technical Education Science, 2014)
Hypocycloid reducer is usually used in devices with high precision such as the industrial robots, the CNC machines and the digital-control equipments, because of its advantages large transmission ratio, compact size, high precision because of backlash reduction. Calculation and design of this gear box are to determine the force distribution rule at contact points between the cylindrical rollers of the planet wheel and hypocycloidal ring gear. It is also necessary to calculate the force impact between rollers of the output shaft and cylindrical rollers in gear matching process. These are the main contents of this paper.